OPTIMISATION, HETEROGENEITY, AND RECYCLABILITY STUDIES OF PS-Pd(CH3) CATALYST IN THE HECK REACTION - SAID, NUR RAHIMAH BINTI; Shamsuddin, N. A. M.; Abdul Rahman, N. A.; Alias, Y. (Journal of Engineering and Technology (JET), 2026)
Polystyrene-supported palladium catalysts have gained significant attention in heterogeneous cross-coupling reactions due to their structural robustness and ease of separation. The present study evaluated the catalytic performance of a polystyrene-supported palladium(II)-hydrazone complex incorporating a methyl substituent (PS-Pd(CH₃)) in the Heck reaction. The optimisation of key reaction parameters including different starting materials (aryl bromide), solvent, catalyst loading, and reaction time was carried out using 1-bromo-4-nitrobenzene and methyl acrylate. Optimal conditions were identified as DMA solvent, 1.0 mmol% catalyst loading, K₂CO₃ base, and 165 °C for 60 minutes, yielding a conversion of 99.8% (TON = 99.8). Hot-filtration and leaching analyses confirmed that the catalytic process predominantly proceeds via a heterogeneous pathway. The catalyst maintained appreciable activity over three consecutive cycles before a decline in performance was observed.